A Translation Shift Analysis On Verb Phrase In Hunger Games 2 (Catching Fire) Subtitling By Erick Jiwono - Kurniawan, Eksa Fredi, Dr. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M.Hum (2015)
The research is to identify the translation shift in Hunger Games 2: Catching Fire and to describe the accuracy of translation. The research type is qualitative research. The writer collects the data by watching the movie of "Hunger Game 2" and its subtitle, taking notes of the subtitle, collecting the data which include the verb phrase, and coding the data and determining the translation shift. Primary data sources in this research consist of data collected from Hunger Game 2 Movie and its subtitle in English and Indonesian. Secondary data is from books, internet, online journals, note, dictionary. The coding data used by the data validity which make the data valid. The techniques of analyzing data are analyzing the form of translation shift in the verb phrase, describing the accurateness of the translation to the theory of translation shift, and making conclusion and suggestion. The results of the research are: 1) the translation shift divided into two types, there are level shift and structure shift. There are 63 data or 36,41 % verb phrase translated into verb. 15 data or 8,67% of verb phrase translated into adjective. 8 data or 4,62 % of verb phrase translated into adverb. 11 data or 6,35 verb phrase translated into noun. There is only one datum from verb phrase translated into preposition. The percentage of verb phrase that involved in level shift is 56,64 % of the whole data. From 173 data, it is found that 48 or 27,74 % belong to structure shift. And in level shift, there are 16 data or 9,2 % of verb phrase translated into adjective phrase. 8 data or 4,62 % of verb phrase translated into adverb phrase. 9 data or 5,20 5of verb phrases translated into noun phrase. 13 data or 7,51 of verb phrases are not translated. 2 data or 1,15 % of negative verb phrase translated into positive. 2) The result of the analysis of the accurateness translation are 101 data or 58.38% as accurate translation, 49 data or 28.32 % as less accurate translation, and 23 data or 13.29% as not accurate translation. Keywords: shift, accurateness, verb phrase, translation